Effect of Urbanization Development on Coral Reef at Marsa Alam Coast, Southern Egyptian Red Sea - ghallab, ahmed (Journal of King Abdulaziz University: Marine Sciences, 2022)
assessment and distribution of coral reefs were studied in three sites in front of Marsa Alam city, Red Sea, Egypt These sites were surveyed mainly for the sensitivity of coral reefs to tourism activities. The survey was conducted using diving equipment throughout the period 2020-2022. line intercepted transect method was used to determined corals and other benthic fauna percentage cover. The results of the current study revealed a significant degradation in the quality of coral reefs in all studied sites, compared to other studies in the Red Sea. While the percentage of live coral cover ranged from 55% in site 1 to 67.6% in site 3 Coral reefs in the studied sites are characterized by higher degraded reefs above the 2 m and 5 m depth zone. Dead coral coverage was 27.8%, 22.9% and 20.6% at sites 1, 2 and 3, respectively. However, the Newly broken colonies were highest at site 1 (2.7%) than at sites 2 (1.4 %) and site 3 (0.9 %). Shannon diversity index H` are all less than 0.70 ranging from 0.65 site 1 to 0.67 at site 3; however, Shannon evenness index J` is in the range between 0.5 site 1 and 0.8 at site 3. Berger-Parker dominance d represents higher variations between sites ranging from 0.25 at site 1 to 0.3 at site 3. Simpson diversity D has lower values ranging from 0.13 at site 1 and Canyon to 0.14 at sites 1 & 2. Margalef diversity M has higher values of diversity but in contrast to other indices, it is lowest in site 1 (0.13) and highest in sites 2 & 3 (0.14). Although Mackintosh diversity D and Mackintosh evenness index E has values lower than those of Margalef, they have a similar variation between sites having lowest values in site 1 and highest value in site 3. Mackintosh D and Mackintosh E are grouped together having the highest % similarity (97.13%), followed by Shannon H` and Shannon J` which are grouped together (92.29%). However, Simpson D and Berger-Parker are grouped together having a % similarity of 71.23%, finally Margalef index is separated in one group having the lowest % similarity with other groups. Values of indices for richness in general are lowest where the study sites recorded a recent damage. There are some variances in variety between sites in this study, which can be explained by the varying pressures that the sites are subjected to (Boumeester 2005). Site 3 is considered as the healthiest site (based on Shannon species diversity H`) while site 1 is the least healthiest of all